2020
DOI: 10.1111/nph.16855
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in branching and crown architecture helps explain how tree diversity increases tropical forest production

Abstract: This article is a Commentary on Guillemot et al. (2020), 228: 1256–1268.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Guillemot et al (2020) used TLS to measure tree structure in the Sardinilla tropical tree diversity manipulation experiment in Panama. They found that trees in more diverse stands not only have larger total biomass, but also have different allocation patterns among aboveground pools, indicating that diverse stands achieve higher biomass through a canopy structure that makes more complete use of incoming light (see also the Commentary by Cushman & Machado, 2020). Remotely sensed data can also complement standard forest monitoring plots.…”
Section: Remote Sensing Measurements To Complement Large-scale Ground...mentioning
confidence: 99%
See 1 more Smart Citation
“…Guillemot et al (2020) used TLS to measure tree structure in the Sardinilla tropical tree diversity manipulation experiment in Panama. They found that trees in more diverse stands not only have larger total biomass, but also have different allocation patterns among aboveground pools, indicating that diverse stands achieve higher biomass through a canopy structure that makes more complete use of incoming light (see also the Commentary by Cushman & Machado, 2020). Remotely sensed data can also complement standard forest monitoring plots.…”
Section: Remote Sensing Measurements To Complement Large-scale Ground...mentioning
confidence: 99%
“…(2017), Coupel‐Ledru et al . (2022), Cushman & Machado (2020), Disney (2019), D'Odorico et al . (2020), Dong et al .…”
mentioning
confidence: 99%